Analisis Pemilihan Strategi Alternatif Pengurangan Bullwhip Effect dengan Menggunakan Metode Fuzzy AHP pada Produk Perishable: Studi Kasus: Holland Bakery - Muhammad Dahlan; Arfandi Ahmad; Andi Pawennari (CV. ALIM'SPUBLISHING, 2026)
Holland Bakery is a company engaged in the bakery industry that sells bread directly to end consumers. The concept of the bullwhip effect is inherent in the supply chain, there is an effect that spreads in the supply chain called the bullwhip effect, Problems that occur in the supply chain of Holland Bakery products that are Perishable quickly damaged so that it causes demand in product inventory causing the bullwhip effect. The purpose of this study is to Identify indicators of the occurrence of the bullwhip effect in the Holland Bakery supply chain using a fishbone diagram and Determine alternative solutions to reduce the bullwhip effect based on the assessment weight of the Fuzzy AHP (Analytical Hierarchy Process) method criteria. The results of this study The results of the identification of the causes of the bullwhip effect in the Holland Bakery supply chain using the fishbone diagram approach there are 6 causes of the bullwhip effect based on the analysis of Demand forecasting, Order batching, Price fluctuations seen from 4 aspects: Humans (man), Methods (method), Materials (material), Machines (machine). The alternative solution selected based on the Fuzzy AHP weighting assessment yielded a weighting score of 0.7696. Alternative B was the first priority to be selected as an alternative solution to reduce the bullwhip effect in the Holland Bakery supply chain.